Microstructure modification of CGDS and HVOF sprayed CoNiCrAlY bond coat remelted by electron beam - Krajňáková, Petra; Čížek, Jan; Čupera, Jan; Hasegawa, Makoto; Dlouhý, Ivo (Elsevier, 2016)
In the present work two techniques are combined to optimize bond coat properties before thermal barrier coating (TBC) application, the cold gas dynamic spraying (CGDS) and electron beam remelting (EB). Results of the work focused on comparison of high velocity oxygen fuel (HVOF) and CGDS CoNiCrAlY bond coats are firstly presented. Than the effect of the electron beam remelting of the CoNiCrAlY coating manufactured by HVOF and CGDS deposition techniques is deeply investigated. The CoNiCrAlY bond coat to Inconel substrate interface displayed locations with very poor bonding, in larger extent for the states prepared by HVOF comparing to CGDS. The bond coats prepared by both ways being EB remelted are typically removal of the defects on the substrate to bond coat interface. The microstructure of the bond coat after this treatment is formed by Inconel fine grain layer being followed by the surface layer consisting of elongated dendritic microstructure. An increased porosity has been observed in interdendritical space in larger extent for CGDS samples.

In the present work two techniques are combined to optimize bond coat properties before thermal barrier coating (TBC) application, the cold gas dynamic spraying (CGDS) and electron beam remelting (EB). Results of the work focused on comparison of high velocity oxygen fuel (HVOF) and CGDS CoNiCrAlY bond coats are firstly presented. Than the effect of the electron beam remelting of the CoNiCrAlY coating manufactured by HVOF and CGDS deposition techniques is deeply investigated. The CoNiCrAlY bond coat to Inconel substrate interface displayed locations with very poor bonding, in larger extent for the states prepared by HVOF comparing to CGDS. The bond coats prepared by both ways being EB remelted are typically removal of the defects on the substrate to bond coat interface. The microstructure of the bond coat after this treatment is formed by Inconel fine grain layer being followed by the surface layer consisting of elongated dendritic microstructure. An increased porosity has been observed in interdendritical space in larger extent for CGDS samples.
Microstructure modification of CGDS and HVOF sprayed CoNiCrAlY bond coat remelted by electron beam
Keywords: CoNiCrAlY; bond coat; thermal spray; electron beam remelting; thermal barrier coating; CoNiCrAlY; bond coat; thermal spray; electron beam remelting; thermal barrier coating